giải phương trình sau:
a) \(4x^2+\left(8x-4\right).\sqrt{x}-1=3x+2\sqrt{2x^2+5x-3}\)
b) \(8x^3-36x^2+\left(1-3x\right)\sqrt{3x-2}-3\sqrt{3x-2}+63x-32=0\)
c) \(2\sqrt[3]{3x-2}-3\sqrt{6-5x}+16=0\)
d) \(\sqrt[3]{x+6}-2\sqrt{x-1}=4-x^2\)
Giải các phương trình:
\(x^2+4\sqrt{x+3}=3x+6\)
\(x+4\sqrt{x+3}+2\sqrt{3-2x}=11\)
\(3x^2-5x+6=2x\sqrt{x^2+x-3}\)
\(\sqrt{2\left(x^4+4\right)}=3x^2-10x+6\)
Giải các phương trình sau:
a) \(\sqrt{x+\sqrt{x-11}}+\sqrt{x-\sqrt{x-11}}=4\).
b) \(\sqrt{x+2+3\sqrt{2x-5}}+\sqrt{x-2-\sqrt{2x-5}}=2\sqrt{2}\)
Giải phương trình sau: \(\sqrt[3]{\frac{x^3-3x-\left(x^2-1\right)\sqrt{x^2-4}}{2}}=2-\sqrt{3}\)
Bài 2. Giải các phương trình sau. a) 3x - 2sqrt(x - 1) = 4 b) sqrt(4x + 1) - sqrt(x + 2) = sqrt(3 - x) c) (sqrt(x - 1) - sqrt(5 - x))(|10 - x| + 2x - 16) = 0
Giải phương trình:
\(\sqrt[3]{x+2}+\sqrt[3]{x^2+3x-5}=\sqrt[3]{x^2+4x-4}+1\)
giải phương trình \(x^2-x+11=3\sqrt{x^2+x+3}+2\sqrt{x^2-3x+6}\)
giải các phương trình sau:
a) \(3x^2-17x+24=\sqrt{x-3}+3\sqrt{5-x}\)
b) \(\sqrt[3]{x+6}-2\sqrt{x-1}=4-x^2\)
Giải các phương trình sau:
a \(x^2-11=0\)
b \(x^2-12x+52=0\)
c \(x^2-3x-28=0\)
d \(x^2-11x+38=0\)
e \(6x^2+71x+175=0\)
f \(x^2-\left(\sqrt{2}+\sqrt{8}\right)x+4=0\)
g\(\left(1+\sqrt{3}\right)x^2-\left(2\sqrt{3}+1\right)x+\sqrt{3}=0\)